2017
DOI: 10.1175/jcli-d-17-0202.1
|View full text |Cite
|
Sign up to set email alerts
|

On How the Middle Atmospheric Residual Circulation Responds to the Solar Cycle Close to the Solstices

Abstract: During high solar activity, the atmosphere receives more energy from the sun, particularly in the form of shortwave radiation. Most notable is the effect in the middle and upper atmosphere, which in general shows a positive temperature response due to physical and chemical processes that are intensified at high solar activity. It is thus surprising that a clear solar cycle signal is absent in the summer polar mesosphere region in spite of it being illuminated around the clock. In this study, it is investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…The temperature response is significant in the upper mesosphere during July and January (Figures a and b), with the exception of a slightly reduced solar response at the highest latitudes in summer. Model studies (Gan et al, ; Karlsson & Kuilman, ; Qian et al, ) have shown a far stronger reduction in the T‐Lα correlation near the polar summer mesopause than is indicated by the observations in Figure , a discrepancy that is currently not understood. The H 2 O‐Lα anticorrelation is significant in the upper mesosphere during July and January (Figures c and d), except for latitudes poleward of ~55° where a weak positive correlation appears.…”
Section: The Missing Solar Cycle Responsementioning
confidence: 86%
See 4 more Smart Citations
“…The temperature response is significant in the upper mesosphere during July and January (Figures a and b), with the exception of a slightly reduced solar response at the highest latitudes in summer. Model studies (Gan et al, ; Karlsson & Kuilman, ; Qian et al, ) have shown a far stronger reduction in the T‐Lα correlation near the polar summer mesopause than is indicated by the observations in Figure , a discrepancy that is currently not understood. The H 2 O‐Lα anticorrelation is significant in the upper mesosphere during July and January (Figures c and d), except for latitudes poleward of ~55° where a weak positive correlation appears.…”
Section: The Missing Solar Cycle Responsementioning
confidence: 86%
“…Future efforts will benefit from model studies to verify the patterns reported here and understand their underlying causes. Given the model results (e.g., Karlsson & Kuilman, ) indicating dynamical feedbacks that damp out solar cycle influences in the polar summer mesosphere, the greater mystery may be the seemingly large solar cycle response before ~2002 and not the recent absence of one. In this regard, there are two relevant but untested suggestions in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations